2002
DOI: 10.1177/016327870202500104
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Cochrane Collaboration’s Central Register of Controlled Clinical Trials

Abstract: The Cochrane Collaboration has established a centralized database of controlled trials and other studies of health care interventions (called CENTRAL) that serves as the best available resource for all those preparing and maintaining systematic reviews or otherwise searching for trials. CENTRAL is available on The Cochrane Library. This article describes the history and methods of CENTRAL's development and the results of an analysis of the current composition of CENTRAL. As of September 2000, CENTRAL contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 12 publications
1
97
0
3
Order By: Relevance
“…However, the search did use the CENTRAL database in the Cochrane Library, which is a comprehensive database of randomized controlled trials identified from a large number of databases without time restriction, as well as the results of handsearches of journals conducted by the Cochrane collaboration (Dickersin et al 2002). It has been suggested that traditional exhaustive search strategies using multiple databases are not cost-effective, as this has already been done for CENTRAL (Royle & Waugh, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the search did use the CENTRAL database in the Cochrane Library, which is a comprehensive database of randomized controlled trials identified from a large number of databases without time restriction, as well as the results of handsearches of journals conducted by the Cochrane collaboration (Dickersin et al 2002). It has been suggested that traditional exhaustive search strategies using multiple databases are not cost-effective, as this has already been done for CENTRAL (Royle & Waugh, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The in-domain monolingual corpora include (cf. Table 2): the Cochrane database of reviews of primary research in human health care and health policy [63], DrugBank -a bioinformatics and cheminformatics resource describing drugs [64], Gene Regulation Event Corpus (GREC) -a semantically annotated English corpus of abstracts of biomedical texts [65], the GENIA corpus of biomedical literature compiled and annotated within the GENIA project [66], the Foundational Model of Anatomy Ontology (FMA) -a knowledge source for biomedical informatics concerned with symbolic representation of the phenotypic structure of the human body [67], English texts extracted from the UMLS Metathesaurus [40], the Patient Information Leaflet Corpus (PIL) -a collection of documents giving instructions to patients about their medication [69], and finally, a large set of texts extracted from HONcode-certified sites (HON) that have been identified by language-detection libraries [70,71] to be English-language [72].…”
Section: In-domain Monolingual Corporamentioning
confidence: 99%
“…15 Medical Subject Heading (MeSH) terms used included rhinosinusitis, sinusitis, and corticosteroids (including dexamethasone, betamethasone, prednisone, and all variations of these terms) and viral and bacterial upper respiratory tract pathogens (full search strategy available from authors). Two authors independently reviewed the titles and abstracts of electronic searches, obtaining full-text articles to assess for relevance where necessary.…”
Section: Search Strategy and Selectionmentioning
confidence: 99%